India Earthquake 8th October 2005, Jammu and Kashmir : Preliminary Damage and Needs Assessment - Asian Development Bank (New Delhi, 2013)
This report provides an assessment of damages and needs resulting from the earthquake that struck India on the 8m of October 2005. It provides a preliminary estimate of the total cost of damage identifies the needs for reconstruction and discusses strategies and guiding principles for the implementation for a program of reconstruction, the whole based on a need to mitigate future impact of natural disasters through the strengthening of disaster risk management. The report was prepared in response to the Government of India (Department of Economic Affairs) and was undertaken by the United Nations, World Bank and the Asian Development Bank. A team of experts drawn from the three institutions visited the worst affected areas of Jammu and Kashmir to undertake the assessment. The assessment mission comprised experts and specialists drawn from all relevant disciplines so as to be able to prepare a multi-sectoral report of damage, loss, recovery and reconstruction options, as comprehensive as possible given the very limited amount of time able to conduct field visits. The assessment team expresses its appreciation to all authorities for their support and assistance in terms of access to information and availability for discussion. Particular thanks are expressed to the Divisional Commissioner and his team for facilitating logistics and security during our stay in Srinagar and for transportation to the affected areas, as well as to District Commissioners and their teams at a local level for providing information and support during the visits themselves. The findings of the assessment, conducted between December 15th and 2200 are presented in this report. They analysis of the team is based on discussions with all relevant authorities and the limited visits to the worst-affected areas as well as analysis of figures provided by authorities on key pre-earthquake data. Given that not all information is even to date available to the assessment team members, and the limited amount of time present in the affected areas themselves, the figures for damage and needs are to be considered as the best estimate possible.